2014
DOI: 10.1097/aog.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Cervical Length Measurement and Fibronectin Testing in Threatened Preterm Labor

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 18 publications
0
33
0
5
Order By: Relevance
“…There is often warning of impending preterm delivery, and interventions can be considered that might prolong gestation or reduce the risk of an adverse outcome by ‘preparing' the fetus, or enabling transfer to a centre with more experience of dealing with problems of prematurity. Cervical length measurement, in combination with fetal fibronectin testing, can help to determine which women are at low risk of delivery within 7 days, and perhaps allow a more judicious use of antenatal treatments [11]. Extremely preterm babies at risk of RDS should be born in centres where appropriate skills are available, as long-term health outcomes are better if they receive their initial neonatal care in tertiary units [12].…”
Section: Prenatal Carementioning
confidence: 99%
“…There is often warning of impending preterm delivery, and interventions can be considered that might prolong gestation or reduce the risk of an adverse outcome by ‘preparing' the fetus, or enabling transfer to a centre with more experience of dealing with problems of prematurity. Cervical length measurement, in combination with fetal fibronectin testing, can help to determine which women are at low risk of delivery within 7 days, and perhaps allow a more judicious use of antenatal treatments [11]. Extremely preterm babies at risk of RDS should be born in centres where appropriate skills are available, as long-term health outcomes are better if they receive their initial neonatal care in tertiary units [12].…”
Section: Prenatal Carementioning
confidence: 99%
“…Several studies, including our nationwide cohort study, have reported promising results of the combination of cervical length and fetal fibronectin measurements to predict preterm delivery within 7 days in symptomatic women [2,11,12]. It is possible that predictions will improve even further when other prognostic features are added to these two measures.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies have reported promising results of combining cervical length and fetal fibronectin measurements to predict spontaneous preterm delivery in symptomatic women, including our own APOSTEL-1 study [2,11,12]. Measuring cervical length and fetal fibronectin has been shown cost-effective by reducing unnecessary healthcare costs without compromising neonatal outcome [27,28].…”
Section: Commentmentioning
confidence: 96%
See 1 more Smart Citation
“…Weiterer Marker, die physiologische von behandlungsbedürftiger Wehentä-tigkeit differenzieren können [11][12][13], sind 4 fetales Fibronektin (fFN), 4 plazentares α-Mikroglobulin-1 (PAMG-1)und 4 phosphoryliertes pIGFBP-1 ("insulin-like growth factor binding protein-1"). …”
Section: Indikation Zur Wehenhemmungunclassified